2012
DOI: 10.1177/0956247812468255
|View full text |Cite
|
Sign up to set email alerts
|

Sanitation survey of two urban slum Muslim communities in the Kumasi metropolis, Ghana

Abstract: The Millennium Development Goals call for a 50 per cent reduction in the proportion of people without sustainable access to safe drinking water and sanitation. Provision of these services by city authorities is often absent in slum(1) settlements in developing countries as these settlements are classified as illegal by city authorities. A field survey was conducted in two urban slums in the Asawase constituency of Kumasi, Ghana to ascertain the extent of "improved" water and sanitation coverage as defined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 14 publications
3
18
1
Order By: Relevance
“…These socio-economic dynamics therefore reveal that there are differences between landlords’ and tenants’ preferences, thus advancing the theory that tenants have less incentive to invest in sanitation facilities because landlords will harness the benefits through rent increments [ 8 , 72 ]. These different preferences have also been reported in studies done in Kampala and Dar es Salaam [ 9 ], as well as in Ghana [ 65 ]. Tenants may not be willing to invest in sanitation because of their “temporary” status, and because they feel it is the landlord’s responsibility.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These socio-economic dynamics therefore reveal that there are differences between landlords’ and tenants’ preferences, thus advancing the theory that tenants have less incentive to invest in sanitation facilities because landlords will harness the benefits through rent increments [ 8 , 72 ]. These different preferences have also been reported in studies done in Kampala and Dar es Salaam [ 9 ], as well as in Ghana [ 65 ]. Tenants may not be willing to invest in sanitation because of their “temporary” status, and because they feel it is the landlord’s responsibility.…”
Section: Discussionsupporting
confidence: 66%
“…The prevalent use of pit latrines is not surprising, since other studies and reports indicate that there are fewer sanitation technologies within Kisumu’s informal settlements, and that pit latrines are used by the majority, while septic tanks serve a small minority [ 48 , 52 , 62 ]. This predominance of pit latrines is common in other informal settlements in Uganda [ 63 ], Tanzania [ 9 , 13 ], Rwanda [ 64 ], Senegal [ 32 ] and Ghana [ 65 ]. Possible users of the few septic tanks in Kisumu’s informal settlements would most likely be home owners, who were purposely left out of this study because they were not rent payers.…”
Section: Discussionmentioning
confidence: 99%
“… 11. Jenkins, M and S Sugden (2006) , “Rethinking sanitation: Lessons and innovation for sustainability and success in the new millennium”, UNDP Human Development Report Office background paper; also Wegelin-Schuringa, M and T Kodo (1997) , “Tenancy and sanitation provision in informal settlements in Nairobi: revisiting the public latrine option”, Environment and Urbanization Vol 9, No 2, pages 181–190; and Adubofour, K, K Obiri-Danso and C Quansah (2013) , “Sanitation survey of two urban slum Muslim communities in the Kumasi metropolis, Ghana”, Environment and Urbanization Vol 25, No 1, pages 189–207. …”
mentioning
confidence: 99%
“…Four sanitation technologies were mentioned by respondents, with the pit latrine being the most commonly used and preferred technology. Studies have shown that use of pit latrines is common in slum settlements in East Africa (Kulabako et al 2010;Omambia 2010;Szántó et al 2012;Isunju et al 2013;Tumwebaze et al 2013;Pieter Van Dijk et al 2014;Jenkins et al 2015;Nakagiri et al 2015;Tsinda et al 2015) and in other African countries such as Ghana (Adubofour et al 2013;Obeng et al 2015), Senegal (Gulyani et al 2010;Scott et al 2013), Zimbabwe (Chinyama et al 2012) and Malawi (Chunga et al 2016). In spite of their common use, pit latrines present a couple of shortcomings.…”
Section: Discussionmentioning
confidence: 99%